Effect of pantoprazole and Helicobacter pylori therapy on uninvestigated dyspeptic patients - Birol Baysal,; Hakan Şentürk,; Omar Masri,; Mukaddes Tozlu,; Yusuf Kayar,; Elif Arabacı,; Ömer Uysal,; Mehmet Sait Buğdacı,; Ali Tüzün İnce, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: This study aimed to test the efficacy of empirical proton pump inhibitor use and Helicobacter pylori therapy for uninvestigated dyspepsia in a population with a high prevalence of H. pylori. Material and Methods: The study had a two-stage design. In the first stage, the efficacy of 4-week pantoprazole treatment was compared with placebo in patients with uninvestigated dyspepsia. In the second stage, the efficacies of 2-week treatment with pantoprazole in H. pylori-negative patients and H. pylori eradication therapy (pantoprazole + amoxicillin + clarithromycin) in H. pylori-positive patients were compared. The primary endpoint was sufficient overall symptom relief (Global Overall Symptom score ≤2; no or minimal symptoms) at the end of treatment. Results: In the first stage, sufficient overall symptom relief was achieved by 25.2% of patients in the pantoprazole group and 15.5% of patients in the placebo group, a difference that was not statistically significant (p=0.06). In the second stage, the rate of sufficient overall symptom relief was higher in the H. pylori therapy group than in the pantoprazole group (37.1% vs. 23.4%; p=0.02). After untreated follow-up, sufficient overall symptom relief remained significantly higher in the H. pylori therapy group than in the pantoprazole group (39.7% vs. 18%; p<0.001). Almost all patients receiving pantoprazole experienced symptom relapse after treatment. Conclusions: This study validated the use of a test-and-treat strategy against H. pylori in uninvestigated dyspepsia, which may be an advisable treatment approach for uninvestigated dyspeptic patients in countries with a high prevalence of H. pylori.